2021
DOI: 10.1177/10935266211013621
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyosarcoma: How Advanced Molecular Methods Are Shaping the Diagnostic and Therapeutic Paradigm

Abstract: For the past 40 years, progress in rhabdomyosarcoma (RMS) has been focused on understanding its molecular basis and characterizing the mutations that drive its tumorigenesis and progression. Genetic predisposition to RMS has allowed discovery of key genetic pathways and driver mutations. Subclassification of RMS into embryonal (ERMS) and alveolar (ARMS) subtypes has shifted from histology to PAX-FOXO1 fusion status, and new driver mutations have been found in spindle cell RMS. Comprehensive molecular profiling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…This is probably explained by the relatively small sample size and the histotypes that were included. The diagnostic value of molecular methods has been demonstrated for certain histotypes, including synovial sarcoma [37], rhabdomyosarcoma [10,38], clear cell sarcoma [39], and desmoid tumors [40]. The numbers of these histotypes, as well as GIST (n = 2), are underrepresented in our cohort.…”
Section: Discussionmentioning
confidence: 94%
“…This is probably explained by the relatively small sample size and the histotypes that were included. The diagnostic value of molecular methods has been demonstrated for certain histotypes, including synovial sarcoma [37], rhabdomyosarcoma [10,38], clear cell sarcoma [39], and desmoid tumors [40]. The numbers of these histotypes, as well as GIST (n = 2), are underrepresented in our cohort.…”
Section: Discussionmentioning
confidence: 94%
“…The aetiology of cervical RMS is currently unclear. Recent studies have found that RMS, especially ERMS, is more common in children with certain genetic syndromes [5]. These patients often have multiple primary cancers, and a possible correlation between ERMS, especially cervical ERMS, and DICER1 pathogenic variants has been found [6][7][8].…”
Section: Aetiology Of Cervical Rmsmentioning
confidence: 99%
“…These patients often have multiple primary cancers, and a possible correlation between ERMS, especially cervical ERMS, and DICER1 pathogenic variants has been found [6][7][8]. PAX-FOXO1 fusions are present in approximately 80% of ARMS, and missense mutations in MYOD1 are the most common molecular alterations in adult spindle cell/sclerosing RMS [5].…”
Section: Aetiology Of Cervical Rmsmentioning
confidence: 99%
“…Beckwith-Wiedemann syndrome, Gorlin syndrome, Costello syndrome, Noonan syndrome, and neurofibromatosis type I. 2,4 RMS has two major subcategories: alveolar and embryonic. Alveolar RMS has a distinct alveolar architecture, with tumor cells nestled between collagenous septa.…”
Section: Introductionmentioning
confidence: 99%